Gollop-Wolfgang Complex: Clinical and Imaging Implications - Vanderberg, Robert Hunter; Block, Thomas; Gates, Thomas; Gomez, Juan (Indian Journal of Radiology and Imaging, 2021)
Gollop-Wolfgang complex is defined as the presence of a distal bifid femur and tibial hemimelia with or without hand ectrodactyly. The condition commonly presents with several skeletal abnormalities and internal organ congenital defects. We hereby report a case with a classical presentation of Gollop-Wolfgang complex.
Keywords: bifid femur; ectrodactyly; Gollop-Wolfgang complex; hemimelia